Incidence of the organizational dynamics in the development of the new knowledge in the universities - Ariza, Yuleida; Monsalve Peláez, Magda Andrea; Gamboa Caicedo, Nery (Corporación Universitaria Americana, 2023)
At present and in the face of the emergence of new technologies with innovative trends in which knowledge is a fundamental axis to promote development in societies, it is necessary to understand the ways of transferring it, making it an added value for companies; that is why this paper aims to study the relationship between organizational dynamics that affect the development of new knowledge in universities, as an internal source to generate competitive advantage. In its preparation, the descriptive method was used, supported by the documentary review, with a qualitative approach, which provides depth to the study, necessary because it is a phenomenon with scarce background and high social impact, justifying its relevance and validating its commitment to social responsibility. As findings, it is emphasized that organizational capacities represent a predominant factor in the development of new knowledge because rethinking implies permanent research processes. It was concluded that within the factors that influence the organizational dynamics for the creation of new knowledge, it is transformational planning, capable of generating actions that respond to the systemic approach of society, whose innovative knowledge provides a variety of solutions to complex problems.